Facing Religious Contemporary Challenges: Redefining the Partnership of Islamic Higher Education and Islamic Religious Instructors in Mainstreaming Religious Moderation - Wildani Hefni; Rizqa Ahmadi (Jurnal Penelitian, 2022)
This article examines the partnership of Islamic higher education with Islamic religious instructors in mainstreaming religious moderation values. This partnership is conducted to face some challenges in contemporary religious understanding. Religious moderation values, such as tolerance, justice, balance, and humanism, become individual and institutional needs. The type of this research is qualitative research using library-based analysis, which obtains the information from news documents and existing partnership documents. The object of this study is the State Islamic University (UIN) Kiai Haji Achmad Siddiq Jember and Islamic Religious Instructors in the Jember regency. This study concludes that the partnership between two institutions supports the mainstreaming of religious moderation values in several forms, including early mapping of religious conflicts, formulating strategies for resolving religious phenomena, and using digital media. These two institutions agreed on several points outlined in their “declaration.” The functions of religious instructors include educative, consultative, informative, and motivational, and Islamic higher education's role is to become a bridge to assist and provide religious education to the community based on religious moderation values, such as tolerance, fairness, and egalitarianism.